2016
DOI: 10.1155/2016/3134919
|View full text |Cite
|
Sign up to set email alerts
|

An Explanation of the Underlying Mechanisms for the In Vitro and In Vivo Antiurolithic Activity of Glechoma longituba

Abstract: Purpose. To use in vitro and in vivo models to evaluate Glechoma longituba extract to provide scientific evidence for this extract's antiurolithic activity. Materials and Methods. Potassium citrate was used as a positive control group. Oxidative stress (OS) markers and the expression of osteopontin (OPN) and kidney injury molecule-1 (KIM-1) were measured to assess the protective effects of Glechoma longituba. Multiple urolithiasis-related biochemical parameters were evaluated in urine and serum. Kidneys were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…For the first two models, an important step in the formation of the stone is endothelial damage [ 9 , 10 , 11 ]. Researchers in pathogenesis of calcium oxalate stone formation have shown that oxalate-induced generation of oxidative stress could play a significant role in endothelial damage [ 12 , 13 ]. Increased quantities of oxalate could trigger the production of reactive oxygen species in kidneys leading to endothelial injury and apoptosis, which could provide sites for crystal formation [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the first two models, an important step in the formation of the stone is endothelial damage [ 9 , 10 , 11 ]. Researchers in pathogenesis of calcium oxalate stone formation have shown that oxalate-induced generation of oxidative stress could play a significant role in endothelial damage [ 12 , 13 ]. Increased quantities of oxalate could trigger the production of reactive oxygen species in kidneys leading to endothelial injury and apoptosis, which could provide sites for crystal formation [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, phenolic acids, such as caffeic, rosmarinic, chlorogenic acids, and flavonoids possess promising antioxidant properties [17][18][19]. Liang et al have shown that Glechoma longituba had anti-urolithic affects via inhibiting urinary stone formation and urolithiasisrelated protein expression levels, and elevating antioxidant levels [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that oxalate-induced oxidative stress could play a significant role in endothelial damage (Joshi, Peck, & Khan, 2013;Liang et al, 2016). The elevated concentration of oxalate could trigger the production of ROS in kidneys leading to endothelial injury and apoptosis, which could provide sites for stone formation (Cikman et al, 2015;Razzaghi, Garrido, Khazraei, Borges, & Firuzi, 2013;Zuo, Khan, Glenton, & Khan, 2011).…”
Section: Therapeutic Roles Of Pentacyclic Triterpenes and Urolithiasismentioning
confidence: 99%